The role of forkhead box A2 in skeletal muscle - Phua, Wendy Wen Ting (2019)
Skeletal muscle accounts over 40% body mass and is widely recognized for their physical function in locomotion and postural support. With its shear mass, skeletal muscle is also the largest metabolic organ and plays essential roles in whole-body energy homeostasis. Skeletal muscle is responsible for over 80% of post-prandial peripheral glucose uptake and a major consumer of fatty acids. Forkhead box A2 (Foxa2), a member of the forkhead box class of DNA-binding transcription factor, is known critical for embryogenic development and organogenesis. Post-natally, Foxa2 regulates genes involved in post-natal lipid and glucose homeostasis. The majority of current literature on Foxa2 focuses on metabolic organs, this include liver, pancreas, and adipose tissue. However, little to none about the expression and the functional role for Foxa2 in skeletal muscle is known. In this thesis, we showed the presence of Foxa2 in skeletal muscle has a tissue-specific regulation and unexpectedly participates to a lesser extent in lipid metabolism. We also found that ligand activation of peroxisome proliferator-activated receptor b/d (PPARb/d) regulates of Foxa2 to mitigate the acute inflammation-associated muscle damage. Here we present PPARb/d, a well-established master regulator of metabolism with anti-inflammatory functions and that Foxa2 plays a cytoprotective role against inflammatory response.